Pelaksanaan Penyuluhan tentang Gangguan Menstruasi dan Pembagian Buku Saku pada Wanita Usia Subur di Desa Penyengat Olak Kec. Jambi Luar Kota Kab. Muaro Jambi Tahun 2019 - Enny Susilawati; Lia Artika Sari (Jurnal Abdimas Kesehatan (JAK), 2021)
Women of reproductive age have many problems or abnormal menstruation, such as menstrual syndrome and irregular menstruation (Johnson, 2004). Women of reproductive age in modern times are often faced with various psychosocial, medical and economic problems, which can cause stress for women who are unable to adapt to external and internal pressures. So stress can be said as an etiologic factor of menstrual disorders. (Kaplan and Manuck, 2004; Wang et al., 2004). Stress is a physiological, psychological response of humans trying to adapt and regulate both internal and external pressures. This community service activity aims to make women of childbearing age aware of the importance of knowing about types of menstrual disorders and how to overcome them. The activities carried out from April 2019, the activities carried out were: implementation of menstrual disorders and the distribution of pocket books to women of childbearing age (WUS) in Penyengat Olak Village, Kec. Jambi Outer City District. Muaro Jambi Year 2019. So that the Puskesmas officers continue to improve counseling, especially about various types of menstrual disorders and how to overcome them